2019
DOI: 10.1109/ted.2018.2882687
|View full text |Cite
|
Sign up to set email alerts
|

Reverse-Conducting Insulated Gate Bipolar Transistor: A Review of Current Technologies

Abstract: The Reverse Conducting IGBT has several benefits over a separate IGBT and diode solution and has the potential to become the dominant device within many power electronic applications; including, but not limited to, motor control, resonant converters, and switch mode power supplies. However, the device inherently suffers from many undesirable design trade-offs which have prevented its widespread use. One of the most critical issues is the snapback seen in the forward conduction characteristic which can prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Nevertheless, there are still some technical and process issues on the semiconductor aspect. The features and present challenges of the RC-IGBT module from the application perspectives are summarised in Table 5 [60][61][62]. Another trend is the sensor integration on a silicon chip for the condition monitoring [63][64][65][66].…”
Section: Development Trend On Si-igbtsmentioning
confidence: 99%
“…Nevertheless, there are still some technical and process issues on the semiconductor aspect. The features and present challenges of the RC-IGBT module from the application perspectives are summarised in Table 5 [60][61][62]. Another trend is the sensor integration on a silicon chip for the condition monitoring [63][64][65][66].…”
Section: Development Trend On Si-igbtsmentioning
confidence: 99%
“…HE RC-IGBT was first proposed in 1987 with a collector shorted, p-channel IGBT [1] building upon the concept in [2], where to integrate the diode structure within the IGBT n+ regions (anode shorts) are implanted into the p-collector region [3], [4]. It has several advantages: a reduction in the overall silicon area compared to a separate IGBT and diode solution; a reduction in module assembly, wafer processing and testing cost as well as improved reliability offered by a reduction in the number of bond wires; the RC-IGBT is more suitable for high junction temperature operation, and there is the possibility of optimising gate signals to allow better trade-off between the onstate voltage drop and the reverse recovery losses of the diode [5]. Yet despite these benefits, widespread use of the RC-IGBT within high voltage, hard switching applications are limited as the device suffers from an undesirable snapback in the currentvoltage characteristics (MOSFET shorting effect) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this alternative SJ device, it was shown that pillar location is independent of the features of the cathode, thus making processing simpler as there is no need for alignment [9]. It also decouples the anode design from the cathode enabling the designer to better control the saturation current and short circuit capability [9], and has the advantage over the AB RC-IGBT that the n/p pillars in the SJ device do not also need to be optimised for breakdown capability [5]. Similar improvements in snapback was reported for this anode SJ implantation, but, as for the cathode-side SJ device, to remove the snapback entirely the SJ implant had to extend through the entire drift region, which cannot be manufactured [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction: The reverse conducting insulated gate bipolar transistor (RC-IGBT) has an integrated antiparallel free-wheeling diode (FWD) in one chip [1]. Compared to the pair of IGBT and FWD, RC-IGBT has lower cost and less parasitic effects, and it is more attractive in power electronic applications [2]. However, the conventional RC-IGBT is not suitable for parallel operation due to its snapback phenomena at forward on-state [2].…”
mentioning
confidence: 99%